1994
DOI: 10.1038/ng1194-236
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary progressive dystonia with marked diurnal fluctuation caused by mutations in the GTP cyclohydrolase I gene

Abstract: Hereditary progressive dystonia with marked diurnal fluctuation (HPD) (also known as dopa responsive dystonia) is a dystonia with onset in childhood that shows a marked response without any side effects to levodopa. Recently the gene for dopa responsive dystonia (DRD) was mapped to chromosome 14q. Here we report that GTP cyclohydrolase I is mapped to 14q22.1-q22.2. The identification of four independent mutations of the gene for GTP cyclohydrolase I in patients with HPD, as well as a marked decrease in the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
403
3
18

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 731 publications
(430 citation statements)
references
References 38 publications
6
403
3
18
Order By: Relevance
“…Genetic studies of autosomal dominant DRD fi rstly revealed linkage to the long arm of chromosome 14 and later showed this to be caused by a heterozygous mutation in the GCH1 gene located on 14q22.1-q22.2 7,8 . This gene has a high degree of variability, and to date more than 100 different mutations have been identifi ed in the GCH1 coding region 5,9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies of autosomal dominant DRD fi rstly revealed linkage to the long arm of chromosome 14 and later showed this to be caused by a heterozygous mutation in the GCH1 gene located on 14q22.1-q22.2 7,8 . This gene has a high degree of variability, and to date more than 100 different mutations have been identifi ed in the GCH1 coding region 5,9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…This gene has a high degree of variability, and to date more than 100 different mutations have been identifi ed in the GCH1 coding region 5,9,10 . The disease is usually confi rmed by means of biochemical tests, and abnormalities of this gene were only observed in 20 to 87% of patients 2,8,9,11,12 . GCH1 is responsible for catalyzing the formation of tetrahydrobiopterin (BH4), an essential cofactor of tyrosine hydroxylase, which is the rate-limiting step for dopamine biosynthesis 2,13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, dystonia is a prominent feature of 'DOPA-responsive dystonia', a disease in which patients have a genetic defect of dopamine synthesis, caused by reduced GTPcyclohydrolase activity (Ichinose et al, 1994;Nagatsu and Ichinose, 1997;Nygaard, 1995;Patel et al, 1995). These patients respond dramatically to treatment with low doses of the dopamine precursor L-DOPA.…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
“…Several related neurological phenotypes of TH deficiency have been described, i.e., L-DOPA-responsive dystonia (DRD) , juvenile parkinsonism [Ludecke et al, 1996], and progressive infantile encephalopathy with L-DOPA-nonresponsive dystonia [Hoffmann et al, 2003], all inherited in a recessive manner. This autosomal recessive form of DRD is different from the more frequent dominant form of DRD (dominant Segawa syndrome) due to GTP cyclohydrolase I mutations [Ichinose et al, 1994;Thöny and Blau, 2006]. Thus far, several deletion and missense mutations, more than 20 noncoding SNPs, and various synonymous coding and nonsynonymous coding SNPs, a splice junction mutation, and at least three promoter mutations have been reported in the TH gene (Supplementary Table S1).…”
Section: Mutations Within Theth Genementioning
confidence: 99%